A layer-by-layer film of chitosan in a taste sensor application - dos Santos, D. S.; Riul, A.; Malmegrim, R. R.; Fonseca, F. J.; Oliveira, O. N.; Mattoso, LHC (Wiley-Blackwell, 2003)
Chitosan is alternated with sulfonated polystyrene (PSS) to build layer-by-layer (LBL) films that are used as sensing units in an electronic tongue. Using impedance spectroscopy as the principle method of detection, an array using chitosan/PSS LBL film and a bare gold electrode as the sensing units was capable of distinguishing the basic tastes - salty, sweet, bitter, and sour - to a concentration below the human threshold. The suitability of chitosan as a sensing material was confirmed by using this sensor to distinguish red wines according to their vintage, vineyard, and brands.
Keywords: biomaterials; dielectric properties; nanolayers; polysaccharides; sensors